A Route Map for substantially improving supply chain dynamics. (1st January 2000) - Towill, Denis R
Traditional supply chains can amplify demand and thereby produce their own internally generated boom-and-bust scenarios. Consequently, there are many real-world examples of businesses experiencing wide swings in both capacity requirements and stock levels. Furthermore such businesses usually find that they may be grossly overstocked with some products simultaneously with having a substantial backlog for other items. This paper reviews the problem areas generating such unwanted supply chain behaviour as experienced in many market sectors. It provides a proven Route Map of actions which will greatly smooth operations to the benefit of all "players" in the supply chain. The Route Map aims to "design-out" undesirable behaviour rather than to try and correct chaotic operation of the supply chain, retrospectively. As a practical example, many of the proposed actions were included in a package of improvement measures applied to a mechanical precision products global supply chain. Results recorded include a 45% reduction in global inventory and the damping of product demand patterns by up to 58%. However, "doing the right thing" is only a necessary, and not a sufficient condition for actually achieving change. Unless there is an associated attitudinal change thereby accepting progress towards the seamless supply chain the reengineering effort is likely to be wasted.